Competence of the Civil Service Police Unit (CSPU) in providing Emergency First Aid Assistance - Widodo Widodo; Sumardino Sumardino; Akhmad Rifai (Universitas Airlangga, 2017)
Introduction: In the year 2014 there were 456 disasters in Indonesia, comprising 227 natural disasters, 197 non-natural disasters and 32 social disasters. The community is expected to be well prepared in accordance with their respective capacities, and this includes the Civil Service Police Unit (CSPU), which must be competent in providing emergency first aid. The aim of this study is to analyse the effect of emergency first aid training on the competence of CSPU in providing emergency first aid assistance in the Surakarta region. Methods: This study used a pre-experimental technique using a pre-post test group design. The sample consisted of 107 respondents who were recruited by total sampling. Variables in this study were competencies in handling emergency first aid assistance including knowledge, attitude and practice. Data were collected by questionnaire and analysed using Wilcoxon signed-rank test with a p-value of 0.05. Results: There were significant differences in scores on knowledge, attitudes, and practice in providing emergency first aid assistance, with a p-value of 0.012 for knowledge, 0.000 for attitude and 0.001 for practice, respectively. Conclusion: Emergency first aid training is urgently needed for CSPU members that are ever directly in charge in the community in any situation. The CSPU must have the first aid competence to support its performance.